Mediating Silence: The Media's Role in Silencing Religious Dialogue Among U.S. Muslims - Alkazemi, Mariam F. (Journal of media and religion, 2015)
Using the spiral of silence as a theoretical framework, survey data were gathered to examine the degree to which the mass media influence dialogue about religion among Muslim Americans. Survey data were collected from members of religious and cultural organizations across the United States in summer 2012. Participants (N = 166) responded to an electronic questionnaire that addressed several variables, including media use, religiosity, willingness to communicate about religion, tolerance for disagreement about religion, and receiver's apprehension about religion. The results show that Muslims who watch more television are less likely to be willing to communicate about religion within the context of an interpersonal relationship. This study contributes to the scholarship of media and religion by providing evidence of the spiral of silence phenomenon when the minority group is a religious one.